Congenital distal ureteric stricture presenting as obstructive megaureter in an infant: a case report - Dayapule, Sreedhar; Kucherlapati, Abhiram; Donthiri, Sandeep; Qazi , Ifrah Ahmad (International Journal of Research in Medical Sciences, 2023)
Congenital distal ureteric stricture is a rare but most important cause of hydro ureteronephrosis in infants presenting as obstructive megaureter. A 8 months old child suffering from recurrent episodes of fever and poor growth had giant hydroureteronephrosis due to distal ureteric stricture. Often misdiagnosed as primary megaureter or pelviureteric junction obstruction, congenital ureteral strictures and valves are the main causes of congenital ureteric obstruction. He was treated with excision of narrow ureteric segment with tapering ureteroplasty and a ureteral reimplantation was performed. This case is presented and discussed with reference to etiology of this rather rare anomaly.